2022
DOI: 10.3390/molecules27113401
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Bile Acids in the Human Body and in the Development of Diseases

Abstract: Bile acids are specific and quantitatively important organic components of bile, which are synthesized by hepatocytes from cholesterol and are involved in the osmotic process that ensures the outflow of bile. Bile acids include many varieties of amphipathic acid steroids. These are molecules that play a major role in the digestion of fats and the intestinal absorption of hydrophobic compounds and are also involved in the regulation of many functions of the liver, cholangiocytes, and extrahepatic tissues, actin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 225 publications
(196 reference statements)
0
8
0
Order By: Relevance
“…DCA has primarily been studied in the context of diseases such as colonic and hepatic cancer [63][64][65] as a carcinogenic molecule. However, due to its ability to bind the nuclear receptors membrane G protein-coupled bile acid receptor-1 (TGR5) and FXR, which are involved in the regulation of certain inflammatory pathways, it also plays an important role in suppressing inflammation as an agonist for these receptors 66 . In a previous study, DCA was reported to confer resistance to influenza and SARS-CoV-2 infection via immunomodulatory interactions with TGR5 and FXR receptors 44 .…”
Section: Discussionmentioning
confidence: 99%
“…DCA has primarily been studied in the context of diseases such as colonic and hepatic cancer [63][64][65] as a carcinogenic molecule. However, due to its ability to bind the nuclear receptors membrane G protein-coupled bile acid receptor-1 (TGR5) and FXR, which are involved in the regulation of certain inflammatory pathways, it also plays an important role in suppressing inflammation as an agonist for these receptors 66 . In a previous study, DCA was reported to confer resistance to influenza and SARS-CoV-2 infection via immunomodulatory interactions with TGR5 and FXR receptors 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac dysfunction is associated with an increase in concentrations of bile acids in the blood during liver diseases. It is possible that bile acids as a ligand can activate FXR, which can play a part in the development of atherosclerosis [ 293 , 294 ].…”
Section: Cyp3a Involvement In Pathological Processesmentioning
confidence: 99%
“…The course of inflammatory responses can be influenced by such CYP3A substrates as bile acids because the latter interact with certain receptors, e.g., FXR, VDR, and LXR [ 293 ]. These receptors are expressed in immune cells such as monocytes, macrophages, natural killer cells, dendritic cells, T- and B-lymphocytes [ 426 ].…”
Section: Cyp3a Involvement In Pathological Processesmentioning
confidence: 99%
“…The osmotic pressure gradient that arises during the secretion of BAs into the bile ducts is one of the most important factors ensuring the proper flow of bile through the liver [ 45 , 57 ]. Due to their detergent properties, BAs can damage the cell membranes of the biliary epithelium and, consequently, damage the liver parenchyma [ 67 , 68 , 69 , 70 ].…”
Section: Bile Acidsmentioning
confidence: 99%
“… they act as emulsifiers, increasing the availability of fats for pancreatic lipases, facilitating the digestion of triacylglycerols in the diet. they enable the intestinal absorption of fat-soluble vitamins [ 56 , 67 , 69 ]. …”
Section: Bile Acidsmentioning
confidence: 99%